Pengaruh Penerapan e-SPT PPh Pasal 21 Pada Efisiensi Pemrosesan Data Perpajakan Bagi Wajib Pajak Badan Yang Terdaftar Di Kantor Pelayanan Pajak Madya Denpasar - asriningsih, dwijana; Noviari, Naniek (E-Jurnal Akuntansi, 2014)
Tax has a very important role , because it is a major source of revenue for the state to fund government spending and development. To improve the quality of tax service to taxpayers and increase the amount of tax revenue innovations were developed, one of which is to develop an electronic reporting of tax payable using SPT (e-SPT). One of the SPT must be reported using e-tax return is e-SPT Income Tax Article 21. The purpose of this study was to determine the effect of e-SPT application of Article 21 Income tax on data processing efficiency of tax for corporate taxpayers registered at Denpasar Tax Office Associate. Respondents of this study were 85 registered corporate taxpayers in Denpasar Tax Office Associate and located in Denpasar area with simple random sampling method. Data was collected through questionnaires and interviews. The analysis technique used is simple linear regression analysis. Based on the results of the analysis found that the implementation of  e-SPT PPh 21 affects the efficiency of data processing for the taxation of corporate taxpayers registered at Denpasar Tax Office Associate.
Keywords: Tax , e - SPT PPh 21 , Data processing efficiency of taxation